2016
DOI: 10.1002/art.39690
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Course of Active Inflammatory and Fatty Lesions in Patients With Early Axial Spondyloarthritis Treated With Infliximab Plus Naproxen as Compared to Naproxen Alone: Results From the Infliximab As First Line Therapy in Patients with Early Active Axial Spondyloarthritis Trial

Abstract: Objective To investigate the course of active inflammatory and fatty lesions seen on magnetic resonance imaging (MRI) in patients with early axial spondyloarthritis (SpA) treated with the tumor necrosis factor (TNF) inhibitor infliximab added to naproxen as compared to those treated with naproxen alone. Methods A total of 158 patients with active axial SpA were randomized (2:1) to receive 28 weeks of treatment with either infliximab 5 mg/kg plus naproxen 1,000 mg/day or placebo plus naproxen 1,000 mg/day. MRI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 15 publications
(22 reference statements)
0
11
0
1
Order By: Relevance
“…Maksymowych et al showed that advanced inflammatory vertebral corner lesions on magnetic resonance imaging (MRI) are more likely to progress to syndesmophytes through a process of fat metaplasia in spite of TNFi treatment, while early lesions could be resolved without progression . In the Infliximab As First Line Therapy in Patients with Early Active Axial Spondyloarthritis Trial, which enrolled patients with axial spondyloarthritis of <3 years duration, ~70% of resolved vertebral inflammatory lesions did not progress to new fatty lesions . These results indicate that early, effective antiinflammatory treatment may reduce radiographic progression in AS.…”
Section: Introductionmentioning
confidence: 99%
“…Maksymowych et al showed that advanced inflammatory vertebral corner lesions on magnetic resonance imaging (MRI) are more likely to progress to syndesmophytes through a process of fat metaplasia in spite of TNFi treatment, while early lesions could be resolved without progression . In the Infliximab As First Line Therapy in Patients with Early Active Axial Spondyloarthritis Trial, which enrolled patients with axial spondyloarthritis of <3 years duration, ~70% of resolved vertebral inflammatory lesions did not progress to new fatty lesions . These results indicate that early, effective antiinflammatory treatment may reduce radiographic progression in AS.…”
Section: Introductionmentioning
confidence: 99%
“…In CANADIAN-AS, 9 new bone formation was more apparent in advanced vertebral corner inflammatory legions (CILs) compared with less advanced CILs. In INFAST, 10,11 there was significantly greater reduction in inflammation with combination therapy (infliximab + naproxen) versus naproxen alone. Conclusions: There is evidence that TNF inhibitors may reduce inflammation in the spine and SI joint, and a relationship exists between inflammation presence and new fatty lesion development, as assessed by MRI in axSpA patients.…”
Section: Poster Presentation Abstractsmentioning
confidence: 99%
“…Results: Four RCTs were included (Table). [5][6][7][8][9][10][11] In ESTHER, 5 there was a greater increase of fatty lesion score in the etanercept versus the sulfasalazine group. A significant relationship between inflammation disappearance and fatty lesion appearance was noted in etanercepttreated patients.…”
Section: 4mentioning
confidence: 99%
See 1 more Smart Citation
“…It is believed that their good efficacy is due to their anti-inflammatory capacity, although the exact mechanism why NSAIDs work so well in the treatment of axSpA is still not known. It could also be shown in several studies in AS that NSAIDs can lower C-reactive protein (CRP) [ 7 , 8 ] and in another axSpA study that NSAIDs can reduce inflammation in the axial skeleton as detected by magnetic resonance imaging (MRI) [ 9 ], although the latter study did not include a placebo group.…”
Section: Nsaidsmentioning
confidence: 99%